Improvement in Divide and Conquer Scheme Using Relay Nodes (International Journal of Engineering and Computer Science, 2014)
A wireless sensor network is a network of large number of sensor nodes, which can perform sensing, computation, and transmission of sensed data. Long distance transmission by sensor nodes is not energy efficient. One approach to extend the network lifetime while protecting network connectivity is to set up a small number of costly, but more powerful relay nodes whose main task is to communicate with other sensor or relay nodes. There are many issues in wireless sensor network like energy consumption, node deployment, network lifetime, etc. In this paper, we focused on the divide and conquer scheme which help to increase the throughput and reduce the packet loss in the network. To overcome these problems a new technique will be proposed.  Experimental results show the throughput and packet loss of all the regions